Green Skills for Future Accountants: Insights from Rempang Eco City Development - Riadi, Sugeng; Gultom , Febbyana Veronica (Universitas Muhammadiyah Yogyakarta, 2026)
This study investigates the green skills required by future accountants over the next two decades within the context of the Rempang Eco City development. Employing a qualitative, phenomenological approach, the research captures the perspectives and experiences of key informants through interviews guided by green skills indicators. The data were analyzed thematically using NVivo 15 to categorize and identify core themes. Findings reveal 14 critical green skills, including waste management, planning, procurement and material management, communication, leadership and teamwork, problem-solving and critical thinking, scientific literacy, operations management, monitoring, cognitive capacity, interpersonal and intrapersonal skills, and competencies in data analysis and information exploration. The results highlight that green skills constitute essential competencies for future accountants in advancing sustainable development. Moreover, complementary certifications—such as regional and urban planning or energy auditing—are recommended to enhance accountants’ contributions to sustainability initiatives. This study contributes by identifying and mapping the green skills required by future accountants to support sustainable development, while providing a foundation for the development of sustainability-oriented accounting education curricula and professional certifications.